Alih Fungsi Lahan Pertanian dan Dampaknya Terhadap Kesejahteraan Petani dan Ketahanan Pangan di Provinsi Bali - I Made Sudarma; Anak Agung Ayu Wulandira Sawitri Djelantik; Geetha Mohan; Indrek Melts; Aki Kadulin; Abd Rahman As syakur (Program Studi Agribisnis, Fakultas Pertanian, Universitas Udayana Jalan PB.Sudirman Denpasar, Bali, Indonesia. Telp: (0361) 223544 Email: soca@unud.ac.id, 2024)
Land conversion has serious implications for food production, the physical environment and the welfare of agricultural and rural communities whose livelihoods depend on their land. The increase in population is not the only cause of problems that are hindering Bali from achieving regional food security. The aim of this research are seeks Identify the determinants influencing the conversion of agricultural land and evaluate the impact of land conversion on the welfare of farmers.what is more worrying is the reduced conversion of agricultural land to non-agricultural uses. Based on the analysis result that the main factors driving land conversion are external and internal factors. The external factors that dominantly encourage conversion land are more promising jobs in other sectors, uncertainty in the price of agricultural products (price fluctuations), difficulty in finding labor in the agricultural sector. From the internal side, factors driving land conversion are difficulties in obtaining water resources, high risk, and economic pressure. The consequences of land conversion found there is an increase of the income farmers on average of Rp 240,650 / acre / month due to farmers. Land conversion does not affect the food security of farming families but affects food supply at the regional and national level. Some suggestions that can be given for minimizing land conversion are strengthening cooperation between subak regulation as a local geneous with government policy and provision of compensation in the form of tax exemption.